As figuras de linguagem na Gramática secundária de Said Ali e na Moderna gramática portuguesa de Evanildo Bechara: um estudo descritivo-analítico - Mendes, Leila Cristina (2010)
This thesis is included in the Portuguese Language s History and Description of the Postgraduate Studies Program at Pontifícia Universidade Católica de São Paulo. Its object of study are the figures of speech presented in the Gramática Secundária da Língua Portuguesa (Portuguese Language Secondary Grammar) written by Manuel Said Ali and Moderna Gramática Portuguesa (Modern Grammar Portuguese) of Evanildo Bechara. This research main purpose is to describe and analyze how the books Gramática Secundária and Moderna Gramática Portuguesa discuss figures of speech. Since we are based in the line of thought of the History of Linguistic Ideas, this research considers the historical, political, social, economic, cultural and educational aspects of the context in which these grammars were built. The methodological procedure used/followed was the theoretical descriptive and analytical study whose stages were effective in finding answers to our goals. The relevance of this research is that both authors have produced grammars which have been reference in researching and teaching Portuguese Language.The results indicated that the authors, each within its historical moment, have known to produce rich, completes and accessible grammars in order to facilitate access to effective and practical knowledge of Portuguese language, clearly showing the importance of figures of speech in the linguistic construction. Notwithstanding, we conclude that this research may be continued, since we have studied only one book of each author and they still offer a rich production to be analyzed